Memória e identidade nos romances de Milton Hatoum - Leite, Sylvia Helena Telarolli de Almeida [UNESP] (My University, 2010)
This article deals with how Milton Hatoum explores aspects of the memory, through the convergence of voices in his four Lusophone novels Tale of a Certain Orient, The Brothers, Ashes of the Amazon and Orphans of Eldorado. A profile of complex characters is constructed through a synthesis of accounts, letters and depositions, as different faces of individuals and society at large are interspersed through memory.

Este artículo trata sobre el modo como Milton Hatoum, en sus cuatro novelas - Relato de un cierto oriente, Dos hermanos, Cenizas del Norte y Huérfanos de Eldorado - explora aspectos de la memoria por medio del entrelazamiento de voces. El perfil de personajes complejos se construye en la fusión de relatos, cartas y testimonios, al intercalar facetas del individuo y de la colectividad por medio de la memoria.

Cet article décrira la façon dont Milton Hatoum dans ces quatre romans - Récit d’un certain Orient, Deux Frères, Cendres d’Amazonie et Orphelins de l’Eldorado -, explore des aspects de la mémoire par des entrecroisements de voix. Le profil de personnages complexes se dessine au moyen de fusion de récits, de lettres et témoignages, intercalant les facettes de l’individu et de la collectivité grâce à la mémoire.

Este artigo trata do modo como Milton Hatoum, em seus quatro romances - Relato de um certo Oriente, Dois irmãos, Cinzas do norte e Órfãos do Eldorado -, explora aspectos da memória por meio do entrecruzamento de vozes. O perfil de personagens complexas se constrói na fusão de relatos, cartas e depoimentos, ao intercalar faces do indivíduo e da coletividade por meio da memória.
Memory and identity in the novels of Milton Hatoum
Memoria e identidad en las novelas de Milton Hatoum
Keywords: Ficção contemporânea; Literatura brasileira; Milton Hatoum